Association between a body shape index and colorectal cancer in US population: a cross-sectional study based on NHANES - Liu, Hui; Kang, Jialu; Liu, Wei; Shen, Yongqing (Frontiers in Nutrition, 2025)
BackgroundColorectal cancer (CRC) is linked to obesity, particularly visceral fat. A more accurate measure of visceral fat accumulation is offered by a body shape index (ABSI). Currently, the direct application of the ABSI to populations with varying ethnic backgrounds might be restricted. Moreover, there is less evidence about the correlation between ABSI and CRC among individuals from different ethnical backgrounds.MethodsA total of 40,998 individuals who took part in the National Health and Nutrition Examination Survey (NHANES) spanning from 2003 to 2023 were subjected to analysis. Logistic regression was utilized to examine the associations between the ABSI and the risk of CRC. In addition, restricted cubic spline curves (RCS) were utilized, and subgroup analyses along with interaction tests were also carried out. The receiver operating characteristic curve (ROC) was employed to predict the risk of CRC relying on various anthropometric indicators.ResultsAfter adjusting for covariates, ABSI demonstrated a positive association with the incidence of CRC (OR = 1.03 [95% CI: 1.01–1.05], p = 0.018). Individuals in the upper quartile of ABSI exhibited a greater prevalence of CRC than those in the lower quartile (OR = 1.88 [95% CI: 1.19–2.96], p = 0.006). RCS analysis indicated a nonlinear correlation between ABSI and CRC (P for nonlinear = 0.030). Subgroup analysis indicated a notable interaction between age and BMI subgroups (interaction p < 0.05), and ROC curves indicated that the ABSI was effective in predicting CRC risk (AUC = 0.658), demonstrating good sensitivity, particularly in individuals under 60 years of age.ConclusionA positive correlation exists between ABSI levels and the increased incidence of CRC among U.S. adults. This is especially true for people under 60 years of age (40–60 years), with a BMI below 25 kg/m2, and those with a BMI of 30 kg/m2 or beyond. ABSI can be used as a simple anthropometric predictor of CRC.